Post-operative radiation therapy with or without chemotherapy for anal squamous cell carcinoma incidentally discovered after local excision: a propensity score matched analysis of retrospective multicenter study - Kim, Kyung Su (Br J Radiol, 2020)
OBJECTIVE: To evaluate the results of post-operative radiation therapy (RT) for anal squamous cell carcinoma (ASCC) incidentally detected after excision, and compare these outcomes with those of definitive RT without excision for exploring the possibility of treatment de-intensification METHODS AND MATERIALS: A total of 25 patients with T1–2N0-1 ASCC who underwent RT following incidental tumor resection were selected from multicenter retrospective database. And, we selected one-to-one matched 25 patients receiving definitive RT from the same database using propensity score matching method, and the outcomes were compared. RESULTS: Median age was 60 years (range, 30–76), and 18 patients (72%) were female. 19 patients (76%) had T0/1 tumors and four patients (16%) had regional lymph node metastases. Hemorrhoidectomy was performed in eight patients (32%) and the others underwent local excision. 12 patients (48%) had microscopic or gross residual diseases. Median RT dose to the primary lesion was 50.4 Gy (range, 40–60). Concurrent chemotherapy was delivered to 23 patients (92%). Median follow-up period was 71 months (range, 4.5–203.1 months). None of the patients showed recurrence during follow-up. However, one patient died after 6 months due to the chemotherapy-related hematologic toxicity. When compared with those patients receiving definitive RT, clinicopathological variables were well-balanced between the two groups. While matched paired patients treated with definitive RT received a higher median RT dose of 54 Gy (range, 45–61.2) and concurrent chemotherapy was given to 22 patients (88%), overall survival was not significantly different (p = 0.262). CONCLUSION: Patients treated with RT for early stage ASCC after local excision showed favorable treatment outcomes. Further study is warranted to justify the de-intensification of the treatment for these patients. ADVANCES IN KNOWLEDGE: Post-operative RT can achieve favorable treatment outcomes in incidental ASCC with residual diseases after local excision.